Severe Pneumonia: Etiology and Outcome in a Tertiary Hospital in Indonesia - Daniel Maranatha, Mawardi; Hamzah (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Severe pneumonia represents a subset of life-threatening pneumonia. The mortality rate ofpatients with severe pneumonia is considerably high. This study aims to determine the etiology and outcomeof severe pneumonia.Methods: An observational prospective study was conducted from September 2017 to September 2018 onpneumonia patients in a tertiary hospital. Clinical and diagnostic evaluations were carried out to assess theseverity of the disease, etiology, comorbidities, and several other factors associated with outcomes.Results: 140 pneumonia patients were evaluated and 41 patients met the severe pneumonia criteria. Apathogen was found in 20 community-acquired pneumonia (CAP) and 13 hospital-acquired pneumonia(HAP). The most frequently isolated pathogen from the sputum culture of patients with either severe CAPor HAP was Acinetobacter baumannii. The mortality rate of severe HAP patients was higher than thatof severe CAP patients (84% vs. 65%), but the difference was nonsignificant. Most of the subjects hadcomorbidities (CAP 75%, HAP 61.6%). Procalcitonin (PCT) and C-reactive protein (CRP) levels in severeCAP were higher than those in severe HAP (PCT 7.7 vs 6.0, p=0.658; CRP 163.1 vs 93.6, p=0.580), but thedifferences were also nonsignificant.Conclusion: The most frequently isolated pathogens from the sputum culture of patients with severepneumonia were Acinetobacter baumanii, which should be considered at the time of diagnosis and empiricalantibiotic therapy. Severe pneumonia was often accompanied by comorbidities, inflammation responsesincrease in both severe CAP and HAP with a high mortality rate.